Alternatives: Methodology for a new politics: changing the 'operating system' of the left after the Greek experience of 2015. Issue 3 (1st September 2016) - Karitzis, Andreas
Abstract: The "SYRIZA experience" provides valuable insights into the inadequacies of the traditional Left methodology to engage effectively with the state and the government within the neoliberal framework. The political imagination and methodology of the Left need to be modified, and I argue that we need a new conceptual and organizational framework of doing politics—both within the state and outside of it—that is relevant to the current situation.